Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1016/0016-6480(89)90005-1
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin cell activity and sodium fluxes in tilapia (Oreochromis mossambicus) after long-term acclimation to acid water

Abstract: Please be advised that this information was generated on 2018-05-12 and may be subject to change.,f NERAL AND COMPARATIVE ENDOCRINOLOGY 75, 3 9^5 (1989) Prolactin Cell Activity and Sodium Fluxes in Tilapia (Oreochromis mossambicus) after Long-Term Acclimation to Acid Water G e r t F l i k ,* J o a n A. v a n d e r V e l d e n , ! H e in C. In tilapia exposed for 3 months to water of pH 4.5, prolactin cell activity, as estimated by ultrastructural morphometry and determination of prolactin synthesis in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
(12 reference statements)
3
13
0
Order By: Relevance
“…In O . mossambicus kept for 4 months under the same controlled condi tions as the mudminnows in the present ex periment, the growth rate was higher at p H 7.0 than at p H 4.5 (Flik et al, 1989). W e consider the higher growth rate of mudmin nows in acid water as further evidence for the exceptional acid tolerance of these fish.…”
Section: A C Id Watersupporting
confidence: 53%
See 4 more Smart Citations
“…In O . mossambicus kept for 4 months under the same controlled condi tions as the mudminnows in the present ex periment, the growth rate was higher at p H 7.0 than at p H 4.5 (Flik et al, 1989). W e consider the higher growth rate of mudmin nows in acid water as further evidence for the exceptional acid tolerance of these fish.…”
Section: A C Id Watersupporting
confidence: 53%
“…H o w ever, at p H 4.0 or higher, the initial drop in plasma sodium is restored in the course of the first week in acid water (Wendelaar Bonga et al, 1984), probably as a result of reduction of the acid-induced increase in branchial permeability to ions. W e have shown that after long-term acclimation the 422 WENDELAAR BONGA ET AL branchial permeability to sodium was even reduced to levels significantly below con trol values (Flik et al, 1989). This decrease was associated with a substantial increase in prolactin cell activity.…”
Section: Western Parts Of Europe and In Northmentioning
confidence: 94%
See 3 more Smart Citations